Innovative eco-safe technologies for residue free fruit production - Kumar, Dinesh; Srivastava, K K; Saroj, P L; Shukla, S K; Ravi, S C (Indian Horticulture, 2026)
Producing good-quality fruits with minimal residue load is crucial for securing better prices in domestic and international markets. Pre-harvest fruit bagging in mango and guava has been standardized as cost-effective and eco-friendly practice for improving fruit quality. Fruits are covered with double-layer nonwoven bags (28 × 20 cm, 80 gsm for mango; 18 × 24 cm, 55 gsm for guava). Bagging is done 28–35 days after fruit set in mango and 35–40 days in guava, and bags remain until harvest. The bag mouth should be closed to prevent pest entry, with perforations to exchange air circulation. Bagging enhances fruit colour, firmness, and shelf life, and significantly reduces pest and disease damage (thrips injuries, fruit fly, physical scratches of fungal spot, etc). Consequently, bagged mango and guava fruits fetch higher market prices and are widely adopted by farmers.